STRATEGIES TO ADDRESS THE PROBLEM OF POOR ACCESSIBILITY TO COUNTERPART FUNDING AND FEDERAL GRANTS. FOR BASIC EDUCATION IN NIGERIA - Adi, Daniel; Zhenseh, Abershi Japhet . (Multi-Disciplinary Research and Development Journals Int'l, 2026)
This position paper examines strategies for addressing the problem of poor accessibility to counterpart funding and federal grants for basic education in Nigeria. Anchored on Stakeholder Theory, the study adopts a qualitative, analytical, and normative research design, relying on an extensive review of policy documents, institutional reports, academic literature, and international best practices in education financing and governance. The paper analyses the structural, legal, administrative, and informational factors responsible for low grant accessibility and highlights the implications of these challenges for educational equity, school effectiveness, and national development. Findings from the analysis indicate that improving access to federal intervention grants requires a multi-dimensional strategy that integrates legal and policy reforms, strengthened transparency and accountability mechanisms, enhanced institutional and administrative capacity, improved communication and awareness, active stakeholder engagement, and the deployment of digital platforms for grant management. The paper argues that reviewing and strengthening the Universal Basic Education (UBE) Act, simplifying grant procedures, building the capacity of school administrators, and fostering community participation are critical to ensuring that intervention funds reach intended beneficiaries and are effectively utilized. The study concludes that equitable and timely access to counterpart funding and federal grants is central to strengthening Nigeria’s basic education system and achieving national education goals. It therefore provides policy-oriented recommendations aimed at promoting inclusive access, efficient utilization, and sustainable management of basic education funding in Nigeria.